Effects of Dietary Protein and Lipid Levels on Growth, Body Composition, Blood Biochemistry, Antioxidant Capacity and Ammonia Excretion of European Grayling (Thymallus thymallus) - Rahimnejad, Samad; Dabrowski, Konrad; Izquierdo, Marisol; Malinovskyi, Oleksandr; Kolářová, Jitka; Policar, Tomas (Frontiers in Marine Science, 2021)
This study evaluated growth, body composition, antioxidant capacity, innate immunity and ammonia excretion of European grayling (Thymallus thymallus) fed diets containing different protein and lipid contents. Six diets were produced to contain 30, 40, or 50% protein and 10 or 20% lipid. Juvenile fish averaging 25.2 ± 0.28 g were stocked into eighteen 450-L circular tanks in a recirculating aquaculture system (RAS) and fed the test diets to satiation twice daily for 12 weeks. Fish weight gain (WG) was enhanced (P < 0.05) as dietary protein increased from 30% (229% WG) to 40% (262% WG) and plateaued thereafter. Enhancing protein and lipid content of diet led to reduced feed intake. Also, feed efficiency was improved by increasing dietary protein (by 40.8%) and lipid (by 16.5%) levels. An interaction of protein and lipid was found on whole-body lipid, and muscle lipid content increased as dietary lipid level increased. Muscle arachidonic acid (ARA), eicosapentaenoic acid (EPA, 20:5n-3) and total n-6 long-chain polyunsaturated fatty acids (LC-PUFA) contents enhanced by increasing dietary protein level. Moreover, increasing fat content of diet led to enhanced muscle linoleic acid, linolenic acid, total monounsaturated fatty acids (MUFA), total n-6, ratio of docosahexaenoic acid (DHA, 22:6n-3) to EPA and n-6/n-3. However, EPA, DHA, total n-6 LC-PUFA, total n-3, total n-3 LC-PUFA, and EPA/ARA ratio decreased at higher dietary lipid level. Serum triglyceride (TG) level and lactate dehydrogenase (LDH) activity decreased as dietary protein level increased. Increasing fat content of diet led to enhanced serum TG, cholesterol and glucose concentrations and reduced alanine aminotransferase, aspartate amino transferase and LDH activities. Serum malondialdehyde concentration was enhanced by increasing both dietary protein and lipid. Furthermore, serum myeloperoxidase activity was enhanced at higher dietary lipid level. Water ammonium nitrogen (NH4+-N) concentration was measured after 5 and 24 h of last feeding, and the results indicated the reduction of ammonia excretion as dietary lipid content increased. These findings suggest that 40% dietary protein can support optimal growth of juvenile European grayling reared in RAS and increasing lipid content from 10 to 20% can improve feed utilization and reduce ammonia excretion to the rearing water.